EL INFINITIVO DE PERFECTO EN LUGAR DEL INFINITIVO DE PRESENTE. (NOTA A PROPERCIO, I, 1,15; I 17,1; II 16,3 Y II 19, 32 - Sánchez Martínez, Félix (Myrtia, 1997)
Propertius uses a perfect infinitive eight times determining the verbs 'nolo', 'volo' or 'possum', when a present infinitive would have been expected. In this paper the different cases are analysed and new, possible explanations are offered.